A unique research infrastructure from the European Organisation for Research and Treatment of Cancer (EORTC) to optimize long-term follow up of patients-the YOU (Your Outcome Update) protocol: Rationale, scope, design and research opportunities. (May 2018) - Liu, Lifang; Collette, Laurence; Lacombe, Denis; Meunier, Françoise; ,
Abstract: The drastic improvement in early detection, cancer treatment and supportive care has changed cancer from a lethal disease to a manageable condition for many patients. In Europe, more than half of cancer patients live beyond the 5 th year after diagnosis. The prolonged survival of patients plead for a better care and support in the life after cancer. However, current survivorship research is fragmented, inefficient, lacking of holistic approach and sustainable funding system, which largely jeopardize the quality of care for cancer survivors. The European Organisation for Research and Treatment of Cancer (EORTC), the oldest international clinical research organization, launched an innovative solution via a research infrastructure named the YOU protocol (Your Outcome Updates). The current paper aims to illustrate the rationale, scope, design and research perspectives of the YOU.